Cerebral malaria is associated with differential cytoadherence to brain endothelial cells. Issue 2 (4th January 2019) - Storm, Janet; Jespersen, Jakob S; Seydel, Karl B; Szestak, Tadge; Mbewe, Maurice; Chisala, Ngawina V; Phula, Patricia; Wang, Christian W; Taylor, Terrie E; Moxon, Christopher A; Lavstsen, Thomas; Craig, Alister G
Abstract: Sequestration of Plasmodium falciparum ‐infected erythrocytes (IE) within the brain microvasculature is a hallmark of cerebral malaria (CM). Using a microchannel flow adhesion assay with TNF‐activated primary human microvascular endothelial cells, we demonstrate that IE isolated from Malawian paediatric CM cases showed increased binding to brain microvascular endothelial cells compared to IE from uncomplicated malaria (UM) cases. Further, UM isolates showed significantly greater adhesion to dermal than to brain microvascular endothelial cells. The major mediator of parasite adhesion is P. falciparum erythrocyte membrane protein 1, encoded by var genes. Higher levels of var gene transcripts predicted to bind host endothelial protein C receptor (EPCR) and ICAM‐1 were detected in CM isolates. These data provide further evidence for differential tissue binding in severe and uncomplicated malaria syndromes, and give additional support to the hypothesis that CM pathology is based on increased cytoadherence of IE in the brain microvasculature. Synopsis: Cytoadherence of Plasmodium falciparum ‐infected erythrocytes (IE) to the endothelial cells lining brain vessels is a hallmark of cerebral malaria (CM). This study shows that the ability of IE to cytoadhere in the brain of patients with CM and uncomplicated malaria is associated with the disease. IE from children with uncomplicated malaria do not bind well to brain endothelial cells, whereas IE from CM patients show high levels of binding. Significant associations in IE binding to brain endothelial cells were seen for both ICAM‐1 and EPCR. PfEMP1 variants containing EPCR‐binding motifs were associated with cerebral malaria. Abstract : Cytoadherence of Plasmodium falciparum ‐infected erythrocytes (IE) to the endothelial cells lining brain vessels is a hallmark of cerebral malaria (CM). This study shows that the ability of IE to cytoadhere in the brain of patients with CM and uncomplicated malaria is associated with the disease.